2022
DOI: 10.3390/cells11020284
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the Prevention of the Calcium Oxalate Urolithiasis

Abstract: Nephrolithiasis ranks third among urological diseases in terms of prevalence, making up about 15% of cases. The continued increase in the incidence of nephrolithiasis is most probably due to changes in eating habits (high protein, sodium, and sugar diets) and lifestyle (reduced physical activity) in all developed countries. Some 80% of all kidney stones cases are oxalate urolithiasis, which is also characterized by the highest risk of recurrence. Frequent relapses of nephrolithiasis contribute to severe compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 127 publications
0
32
0
Order By: Relevance
“…Besides, the different chemical characteristics of oxalic acid and citrate, including solubility and dissociation constants, could be the possible cause of the conversion of CaOx to CaP. Urinary oxalic acid and citrate metabolism interact, though the mechanism is still uncertain, and can be influenced by several factors, including hyperuricemia, urinary upper metastable limit osmolality, and the microbiota [ 30 , 31 , 32 ]. Although we could not demonstrate an increase in urinary pH in the present study, we found that renal OPN expression significantly increased after statin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the different chemical characteristics of oxalic acid and citrate, including solubility and dissociation constants, could be the possible cause of the conversion of CaOx to CaP. Urinary oxalic acid and citrate metabolism interact, though the mechanism is still uncertain, and can be influenced by several factors, including hyperuricemia, urinary upper metastable limit osmolality, and the microbiota [ 30 , 31 , 32 ]. Although we could not demonstrate an increase in urinary pH in the present study, we found that renal OPN expression significantly increased after statin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The two bacterial probiotics and C. utilis are approved for human consumption by FDA [ 26 , 27 ] in addition, S. cerevisiae is classified as biosafety level 1 [ 28 ]. Thus, no biosecurity-related problems will occur as long as the standard microbiological practices are followed.…”
Section: Methodsmentioning
confidence: 99%
“…rhamnosus GG diminishes the oxalates content of food in vitro. Currently, a number of probiotics are developed to prevent calcium oxalate urolithiasis [ 338 ].…”
Section: Lab In Detoxication Of Food From Natural Antinutrientsmentioning
confidence: 99%